Perspective on Agapeic Ethic and Creation Care - Loveday Chigozie Onyezonwu; Ucheawaji Godfrey Josiah (Religions)
Ongoing discussions on creation care and agapeic ethic have paid less attention to the interplay between love, creation, waste management challenges, and mission. This paper, therefore, discusses a missional perspective of agapeic ethic as a ground norm for eco-theology and motivation for eco-care (especially proper waste management). An attempt is made to discuss the concept and dimensions of love and the nexus between love, creation, and missional purpose. This paper adopts a non-participant observation of refuse collection as carried out by refuse collectors, the waste disposal practices of people, and the waste handling and disposal practices of selected churches. This research was conducted across Port Harcourt City, Obio Akpor, Ogba/Egbema/Ndoni, Oyibo, and Eleme municipal areas of Rivers State, Nigeria. The churches observed include Protestant Churches (Seventh-Day Adventist Church, Church of Nigeria that is Anglican Communion, and Church of Jesus Christ of Latter-Day Saints); the Roman Catholic Church; Pentecostal Churches (such as Salvation Ministries Worldwide, Redeemed Christian Church of God, and Deeper Life Bible Church); and African Indigenous Churches (namely, the Christ Apostolic Church, Cherubim and Seraphim, and Celestial Church of Christ). The information gathered was critically analysed and used in measuring stakeholders’ disposition to and understanding of the research focus. Ecological liberation hermeneutics was adopted as an interpretative framework, while the eco-justice principles of interconnectedness and purpose were engaged to foreground the underlying issues in this study. This paper argued that Christians’ involvement in proper waste management, keeping both private and public spaces clean, is a morally and divinely imposed duty and a practical testimonial of their love for God, their fellow human beings, and non-human others. This is a fulfilment of the mission where Christian love (agape) serves as an ethical principle of inflicting ‘no harm’ to humans or non-human others.